EFFECT OF INTEGRATED NUTRIENT MANAGEMENT ON PRODUCTIVITY, QUALITY AND NUTRIENT UPTAKE BY INDIAN MUSTARD AND THEIR RESIDUAL EFFECT ON PIGEONPEA - SHIVRAN, R.K.; GIRI, GAJENDRA (Annals of Agricultural Research, 2014)
A field experiment was conducted during rabi and kharif seasons of 2002-03 and 2003-04 on nutrient management aspect of mustard-pigeonpea sequence at New Delhi. The application of RDF to mustard produced significantly higher seed and stover yield of mustard. However, it remained on par with half RDF + PSB + Pruteus vulgaris. Pigeonpea produced significantly higher grain and stalk with the application of half RDF + PSB + Pruteus vulgaris in preceding mustard crop. Oil content in mustard was not influenced by the application of fertilizer nutrients, whereas oil yield was significantly higher with the application of half RDF +PSB + Pruteus vulgaris over control, half RDF and 40 kg N/ ha + PSB. Significantly higher protein content (19.3%) was obtained with the application of RDF over control, half RDF and 40 kg N/ha +PSB, whereas it remained on par with half RDF + PSB + Pruteus vulgaris. The higher removal of N and P by mustard was recorded with the application RDF over control, half RDF and 40 kg N/ha + PSB, but it remained on par with half RDF + PSB + Pruteus vulgaris. Pigeonpea removed significantly higher N and P from the application of half RDF + PSB + Pruteus vulgaris in preceding mustard crop.